PENGARUH PERBANDINGAN UBI JALAR UNGU (Ipomoea batatas var Ayamurasaki ) DAN TERIGU TERHADAP KARAKTERISTIK KUE PIA - Anita Putri, Maya; Selamet Duniaji, Agus; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
This study aims to determine the effect of the comparison of purple sweet potato and wheat on characteristics of  pia cake and to determine the right ratio of purple sweet potato and wheat to produce pia cake with the best characteristics. The experimental design used was completely randomized design (CRD) by treatment with purple sweet potato in a row as follows: 15%, 20%, 25%, 30%. Each treatment was repeated four times to obtain 16 experimental units. The variables measured in this study include water content, ash content, protein content, fat content, carbohydrate content and sensory evaluation which includes the texture is done with test scores, as well as color, flavor, aroma and overall acceptance. From the analysis of the above variables, the best treatment is taken and analyzed the levels of anthocyanins with a pH differential method. The results showed that the treatment comparison purple sweet potato and wheat effect on water content, protein content, fat content, and carbohydrate content and the sensory properties of pia cake (color, flavor, texture, and overall acceptance). ). However, did not found any significant effect on ash content, aroma and flavor. The best characteristic of pia cake was obtained on treatment of purple sweet potato and wheat ratio of 25% : 75% with 23.12% moisture content, ash content of 0.77%, 8.09% protein content, fat content 8.78%, 58.80% carbohydrate levels and levels of 0.51% anthocyanins. Sensory properties of the pia cake were color of 5.8 (like), aroma of 5.2 (rather  like), taste of 5.6 (like), texture of 6.05 (like) and overall acceptance of 6,55 (really like).
Keywords: purple sweet potato,wheat , pia cake